Symptoms in smokers with preserved pulmonary function: Frederik Trinkmann, M.D., Thomas Henzler, M.D., Joachim Saur, M.D. - Trinkmann, Frederik; Henzler, Thomas; Saur, Joachim (The New England journal of medicine, 2016)
Correspondence from The New England Journal of Medicine — Symptoms in Smokers with Preserved Pulmonary Function
Gesehen am 21.01.2019